2013
DOI: 10.1096/fj.13-233098
|View full text |Cite
|
Sign up to set email alerts
|

Irradiance encoding in the suprachiasmatic nuclei by rod and cone photoreceptors

Abstract: Light information is transmitted to the central clock of the suprachiasmatic nuclei (SCN) for daily synchronization to the external solar cycle. Essential for synchronization is the capacity of SCN neurons to respond in a sustained and irradiance‐dependent manner to light. Melanopsin has been considered to mediate this photosensory task of irradiance detection. By contrast, the contribution of the classical photoreceptors in irradiance encoding is less clear. Here we investigate the role of classical photorece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 37 publications
3
53
0
Order By: Relevance
“…Bright continuous illumination evokes a sustained depolarization in ipRGCs that encodes stimulus energy. This sets these cells apart from all other photoreceptors, which are less sensitive to encode irradiance and thus to represent ambient light intensity over days and months . These properties are well suited to nondirectional detection of gross environmental illumination essential for integrated circadian, neuroendocrine and neurobehavioral effects .…”
Section: The Advent Of the Circadian Photoreceptormentioning
confidence: 99%
“…Bright continuous illumination evokes a sustained depolarization in ipRGCs that encodes stimulus energy. This sets these cells apart from all other photoreceptors, which are less sensitive to encode irradiance and thus to represent ambient light intensity over days and months . These properties are well suited to nondirectional detection of gross environmental illumination essential for integrated circadian, neuroendocrine and neurobehavioral effects .…”
Section: The Advent Of the Circadian Photoreceptormentioning
confidence: 99%
“…Additionally, it has been suggested that melanopsin mediates persistent light detection in ipRGCs (Altimus et al, 2008; Gooley et al, 2012; Lupi et al, 2008; Mrosovsky and Hattar, 2003; Zhu et al, 2007) because melanopsin phototransduction is relatively slow to initiate but stable for minutes to hours (Berson et al, 2002; Gooley et al, 2012; Wong, 2012). However, animals lacking melanopsin still retain sustained light responses in ipRGCs and their central targets (Schmidt et al, 2014; van Diepen et al, 2013; Wong, 2012) and relatively normal circadian photoentrainment (Panda et al, 2002; Ruby et al, 2002) and PLR (Lucas et al, 2003; Xue et al, 2011). In total, it remains unclear how ipRGCs utilize each distinct photoreceptive input, especially across the environmental range of light intensities and durations.…”
Section: Introductionmentioning
confidence: 99%
“…Because there is a delay of 30–40 ms before visually evoked activity becomes first detectable within the SCN and LGN (van Diepen et al . ; Howarth et al . ; Walmsley & Brown, ), we reasoned that the first pulse of these stimulus trains should be sufficient to increase the inhibitory influence of the GHT prior to the arrival of any retinal input.…”
Section: Resultsmentioning
confidence: 99%